2002
DOI: 10.1080/080352502760311584
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled and nasal nitric oxide in mechanically ventilated preterm and term newborns

Abstract: A novel method for measurement of exhaled NO of an intubated newborn is presented. The possible association of exhaled NO concentration with the development of chronic lung disease remains to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…4 It has also been detected among the gases exhaled by neonates receiving mechanical ventilation. [5][6][7][8][9][10] If BPD appears in the evolution of a preterm survivor, it can be expected that eNO will already be raised in the first days of life, when these preterm infants are usually intubated and receive mechanical ventilation. Recently Roiha et al 11 and Williams et al 12 have reported different results in eNO in BPD: a lower NO output in infants breathing spontaneously and higher exhaled NO peak levels in ventilated infants, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…4 It has also been detected among the gases exhaled by neonates receiving mechanical ventilation. [5][6][7][8][9][10] If BPD appears in the evolution of a preterm survivor, it can be expected that eNO will already be raised in the first days of life, when these preterm infants are usually intubated and receive mechanical ventilation. Recently Roiha et al 11 and Williams et al 12 have reported different results in eNO in BPD: a lower NO output in infants breathing spontaneously and higher exhaled NO peak levels in ventilated infants, respectively.…”
Section: Introductionmentioning
confidence: 99%